2000
DOI: 10.1590/s0102-09352000000100018
|View full text |Cite
|
Sign up to set email alerts
|

Análise de alguns critérios de seleção para características de crescimento na raça Nelore

Abstract: Foram obtidas estimativas de parâmetros genéticos para peso ao nascimento (PN) e ao sobreano (PSOB), ganhos de peso pré- (GPNDES) e pós-desmama (GP345), dias para 160 (D160) e 300kg (D300) de peso vivo, e taxas de crescimento relativo pré- (TCR1) e pós-desmama (TCR2), utilizando 60.470 animais Nelore. Adotou-se o método REML, sob modelo animal. Para características pré-desmama (PN, GPNDES, D160 e TCR1), o modelo incluiu efeitos aleatórios de animal, aditivo materno, de ambiente permanente de vaca e de resíduo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
0
34

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 5 publications
7
3
0
34
Order By: Relevance
“…This hypothesis is supported by the environmental correlation estimate between GBW and GWY (20.17 6 0.016; Table 5), indicating weak antagonism between environmental and non-additive genetic effects that act on the two traits. However, this result agrees with Cardoso et al (2004), Marcondes et al (2000) and Sarmento et al (2003) who reported genetic correlation estimates of 0.23, 0.23 and 0.22, respectively, between pre-and postweaning weight gains.…”
Section: Resultssupporting
confidence: 91%
“…This hypothesis is supported by the environmental correlation estimate between GBW and GWY (20.17 6 0.016; Table 5), indicating weak antagonism between environmental and non-additive genetic effects that act on the two traits. However, this result agrees with Cardoso et al (2004), Marcondes et al (2000) and Sarmento et al (2003) who reported genetic correlation estimates of 0.23, 0.23 and 0.22, respectively, between pre-and postweaning weight gains.…”
Section: Resultssupporting
confidence: 91%
“…Traditionally, features such as body weights and weight gains have been used as selection criteria in various breeding programs for cattle, because they had heritabilities ranging from 0.26 to 0.42 (Marcondes et al, 2000), therefore, with potential to respond effectively to the selection. However, if it is solely based on weight at certain ages and/ or weight gain between two ages, it may prove to be insufficient for the improvement of carcass quality (Kippert et al, 2006), specifically in relation to weight components, as outlined by Long (1973) to propose the Ankony System Evaluation, considering that the breeding program, based solely on weight gain, would be inadequate to meet actual market demands.…”
Section: Introductionmentioning
confidence: 99%
“…O valor estimado sem a inclusão da covariância no modelo foi similar ao encontrado por Malhado et al (2003) para a raça Nelore (0,06 ± 0,02) e, quando considerada a covariância, foi similar ao relatado por Sarmento et al (2003) para a raça Nelore (0,29 ± 0,09), todavia, foi aproximadamente 77, 18 e 27% maior que os relatados por Marcondes et al (2000), Malhado et al (2003), de 18 e 0,05 ± 0,01, respectivamente, ambos para a raça Nelore, e por Cardoso et al (2001) para a raça Angus (0,16). Ressalta-se que Sarmento et al (2003) encontraram valores para a herdabilidade materna Tabela 4 -Componentes de (co)variância e parâmetros genéticos para ganho médio diário do nascimento à desmama (GMDND) e ganho médio diário da desmama ao sobreano (GMDDS) maiores que para a herdabilidade direta, pois espera-se que os genes do bezerro tenham maior influência sobre seu desenvolvimento que os da mãe.…”
Section: Resultsunclassified
“…Esses valores foram próximos aos relatados por Cardoso et al(2004) para a raça Angus (0,20), porém superiores aos descritos por Wilson et al (1986) para as raças Angus e Hereford nos Estados Unidos (0,15 e 0,16), e por Marcondes et al (2000) e Malhado et al (2003), entre 0,08 e 0,11 e de 0,14 ± 0,02 para a raça Nelore.…”
Section: Resultsunclassified
See 1 more Smart Citation